The exchange rate pass-through to inflation, inflation persistence, and threshold inflation rate of West African commonwealth countries - Danlami, Ibrahim Abdulhamid (2019)
High inflation rate and currency devaluation prevailed to be among the everyday challenges of West African Commonwealth Countries (WACCs). Additionally, the majority of the WACCs are unable to curtail and maintain inflation rate at single digit, for registering meaningful economic growth and development. This study aims to analyze the exchange rate pass-through (ERPT) to inflation of WACCs during 1980 – 2016, examine the inflation persistence of WACCS, and establish a threshold-inflation rate by which it is inimical to the economic growth of WACCs during 1970 – 2016. Data were analyzed using Autoregressive Distributed Lag Model (ARDL), Autoregressive (AR) Model, and the Conventional Threshold Model of regime-switching. The ARDL results show that during the short-run, the existence of immediate and complete ERPT is discovered in Ghana, the Gambia and Sierra Leone, whereas no ERPT in Nigeria. The long-run results reveal the existence of complete and positive ERPT in all countries. The AR result shows that high persistence inflation is associated with the first-year lag inflation rate in all the countries in addition to the second year-lag inflation of the Gambia alone. Meanwhile, in Nigeria, the second-year lag inflation is associated with low inflation persistence. It is the third-year lag inflation rate that has an association with low inflation persistence in the Gambia. The results of the threshold model indicate that the lower threshold inflation rates of WACCs are single-digit in all the WACCs except Nigeria, which has double-digit, while the upper threshold inflation rates are double-digit in Nigeria and Ghana and single-digit in the Gambia and Sierra Leone. This study suggests import substitutions and export promotions programs to stabilize exchange rate. Targeted inflation rates are achievable if the inflation-targeting policy is strengthened.